2013
DOI: 10.1002/pi.4493
|View full text |Cite
|
Sign up to set email alerts
|

Blends of recycled polycarbonate and acrylonitrile-butadiene-styrene: comparing the effect of reactive compatibilizers on mechanical and morphological properties

Abstract: Blends of recycled polycarbonate (PC) and acrylonitrile-butadiene-styrene (ABS) were prepared and some mechanical and morphological properties were investigated. To compatibilize these blends, ABS-g-(maleic anhydride) (ABS-g-MA) and (ethylene-vinyl acetate)-g-(maleic anhydride) (EVA-g-MA) with similar degree of grafting of 1.5% were used. To compare the effect of the type of compatibilizer on mechanical properties, blends were prepared using 3, 5 and 10 phr of each compatibilizer. A co-rotating twin-screw extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 32 publications
2
43
0
3
Order By: Relevance
“…The limiting oxygen index (LOI) tests were carried out by using an XZT-100A oxygen index test instrument (Chengde Jiande Test Instrument Co. Ltd, China) based on the standard LOI test ASTM D 2863-97. The dimensions of the specimens were 127 × 10 × 10 mm 3 .…”
Section: Limiting Oxygen Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The limiting oxygen index (LOI) tests were carried out by using an XZT-100A oxygen index test instrument (Chengde Jiande Test Instrument Co. Ltd, China) based on the standard LOI test ASTM D 2863-97. The dimensions of the specimens were 127 × 10 × 10 mm 3 .…”
Section: Limiting Oxygen Indexmentioning
confidence: 99%
“…Acrylonitrile‐butadiene‐styrene copolymer (ABS) is a versatile thermoplastic engineering plastic which is extensively used in many fields, such as the electronics and electrical industry, traffic, construction, automobile parts, toys, office supplies etc . The application for ABS is mainly ascribed to its outstanding advantages in insulation, processing, shining surfaces, thermal stability, mechanical strength, resistance to oil, resistance to weather and improved impact strength .…”
Section: Introductionmentioning
confidence: 99%
“…The existence of partial miscibility between ABS and PC [44] constituted the premise recycling the mixed blend of polymers recovered from WEEE. To obtain ABS/PC composites (70:30) with a similar or higher impact strength than virgin ABS, it is necessary to use compatibilizers like ABS-g-MA, PP-g-MA, SEBS-g-MA, EVA-g-MA in a proportion of 1-20% [33,35,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Balart et al (2005) investigated the effect of previous degradation and partial miscibility of ABS/PC blends to their mechanical performance. Farzadfar et al (2013) compatibilised recycled PC and ABS using ABS-g-MAH and ethylene-vinyl-acetate-grafted-maleic anhydride (EVA-g-MAH) and observed that EVA-g-MAH increases the impact strength in comparison with ABS-g-MAH. Khan et al (2007) concluded that recycled PC can be used as an additive for virgin or recycled ABS, as a means of giving flame resistance to ABS in high-value applications.…”
Section: Introductionmentioning
confidence: 99%